2021
DOI: 10.3390/math9182303
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities: Experiences of Mathematics Lecturers Engaged in Emergency Remote Teaching during the COVID-19 Pandemic

Abstract: In this paper, we consider the experiences of mathematics lecturers in higher education and how they moved to emergency remote teaching during the initial university closures due to the COVID-19 pandemic. An online survey was conducted in May–June 2020 which received 257 replies from respondents based in 29 countries. We report on the particular challenges mathematics lecturers perceive there to be around teaching mathematics remotely, as well as any advantages or disadvantages of teaching mathematics online t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
(31 reference statements)
0
29
1
4
Order By: Relevance
“…The result of the present study can be compared with 10 of these relevant papers [68][69][70][71][72][73][74][75][76][77]. While other researchers have analyzed the effects of ERT on high school teachers [68], state universities [69], and the challenges faced by educational institutions [70], for the proposed model, the developed EvalMathI system was tested to be able to answer questions Q1-Q4, questions that support the development of the model for the evaluation system (LAEM), and also validate the software instrument called EvalMathI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The result of the present study can be compared with 10 of these relevant papers [68][69][70][71][72][73][74][75][76][77]. While other researchers have analyzed the effects of ERT on high school teachers [68], state universities [69], and the challenges faced by educational institutions [70], for the proposed model, the developed EvalMathI system was tested to be able to answer questions Q1-Q4, questions that support the development of the model for the evaluation system (LAEM), and also validate the software instrument called EvalMathI.…”
Section: Discussionmentioning
confidence: 94%
“…In another study [ 73 ], the authors dealt with the evaluation of the quality of courses in ERT situations, proposing a dashboard of indicators for decision making. However, the present study found results in the content of each course evaluated through EvalMathI in terms of the intra- and interdisciplinary relationship and the intra- and intercurricular relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies tried to explain the impact of the rapid transition to online mathematics teaching during the pandemic on students' academic development [12][13][14][15][16][17]24,26,28]. In April 2021, Soesanto et al [9] encouraged researchers to bridge the still large research gap regarding the causality of implementing online mathematics learning in times of crisis in order to contribute to developing pedagogical strategies to improve university students' mathematics performance and attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation showed that the application of STEM online learning has helped to increase students' creativity and the rate of STEM research by both students and faculty members. The findings of [26] indicate that for many mathematics lecturers in higher education, the move to online teaching has been a beneficial experience that will impact their future teaching.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…More than 30% of the responses came from mathematicians working in Ireland. The results of the analysis of the survey data have been published in [24], [25], [26] and [27].…”
Section: The Lecturers' Perspectivementioning
confidence: 99%